In-situ thermal image correlation with mechanical properties of nylon-12 in SLS. Issue 5 (15th August 2016) - Wroe, William Walker; Gladstone, Jessica; Phillips, Tim; Fish, Scott; Beaman, Joseph; McElroy, Austin
Abstract : Purpose: This paper aims to establish a method to verify in real time the quality of a part being built using Selective Laser Sintering (SLS). Design/methodology/approach: A SLS build of 30 Nylon 12 tensile bars was done while using an infrared camera to record the thermal history of each bar. The thermal history was then compared to the ultimate tensile strength (UTS) of each bar. In addition, an attempt was made to identify where the fracture of each bar occurred based on its thermal history. Findings: Several analysis techniques were used to compare the thermal history of each bar to its UTS. The strongest correlation found was 0.746. In addition, multiple strategies for predicting the break location where used, with the most successful making a correct prediction on 46 per cent of the bars. Originality/value: This paper studies the feasibility of in-situ build verification, a technique that if successful would greatly help the further adoption of SLS as a method of manufacturing.